Sensor databases from digital plot Chiquimula, Guatemala - 2024 - Estrada Vargas, Oscar Hernan; Jimenez Rodas, Daniel Ricardo; Ramos Solorzano, Gresia Dalal; Martinez Salgado, Jesus David (2024)
These are data collected from climate and soil sensors in the digital maize plot at San Carlos University, CUNORI, which primarily aim to provide crucial information about the conditions affecting crop development. This data enables farmers, researchers, and academics to better understand how digital technologies can improve the productivity and sustainability of agricultural systemsThese are data collected from climate and soil sensors in the digital maize plot at San Carlos University, CUNORI, which primarily aim to provide crucial information about the conditions affecting crop development. This data enables farmers, researchers, and academics to better understand how digital technologies can improve the productivity and sustainability of agricultural systems Metodology:The data is extracted from three weather stations and one soil probe device using USB interfaceThe data is extracted from three weather stations and one soil probe device using USB interface